Towards establishment of diagnostic reference levels based on clinical indication in the state of Qatar. (2020) - AlNaemi, Huda; Tsapaki, Virginia; Omar, Ahmed J.; AlKuwari, Maryam; AlObadli, Amal; Alkhazzam, Shady; Aly, Antar; Kharita, Mohammad Hassan
Highlights: This is the first study in the Asian region and one of the very few that established DRLs based on clinical indication for CT. Standardized CI nomenclature must be established as there are no guidelines for accurate comparison between studies on CT patient exposure. The established clinical DRL values for CT will further facilitate patient dose optimization and quality improvement process HMC in Qatar. Abstract: Objectives: The objectives of this study were to: 1) evaluate patient radiation exposure in CT and 2) establish CT Diagnostic Reference Levels (DRL)s based on clinical indication (CI) in Qatar. Materials and Methods: Patient data for 13 CIs were collected using specially designed collection forms from the dose management software (DMS) of Hamad Medical Corporation (HMC), the main Qatar healthcare provider. The methodology described in the International Commission on Radiological Protection (ICRP) Report 135 was followed to establish national clinical DRLs in terms of Volumetric Computed Tomography Dose Index (CTDIvol) and total Dose Length Product (DLPt). Effective dose (Ef) was estimated by DMS using DLPt and appropriate conversion factors and was analyzed for comparison purposes. Results: Data were retrospectively collected for 896 adult patients undergoing CT examinations in 4 hospitals and 7 CT scanners. CT for Diffuse infiltrative lung disease imparted the lowest radiation in terms of CTDIvol (5 mGy), DLPt (181 mGy.cm) and Ef (3.6 mSv). Total body CT for severe trauma imparted the highest DLPt (3137 mGy.cm) and Ef (38.6 mSv) of all CIs with a CTDIvol of 15 mGy. Rounded Third quartile CTDIvol and DLPt values were defined as the Qatar CT clinical DRLs. Comparison was limited due to sparse international literature. When this was possible data were lower or comparable with other studies. Conclusions: This is the first study reporting national clinical DRLs in Asia and second one internationally after UK. For accurate comparison between studies, systemized CI nomenclature must be followed by researchers.